2021
DOI: 10.1002/jaba.818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telehealth‐mediated behavioral assessments and interventions on client outcomes: A quality review

Abstract: The purpose of this review was to evaluate the quality of research focused on the effects of telehealth-mediated behavior-analytic assessments and interventions on client outcomes. The majority of studies utilized a single-case methodology (n = 44; 81%), while 10 studies (19%) used a group design. Of the 246 single-case designs, 99 (40%) met design standards with or without reservation. For the 10 group design studies, 7 (70%) met the design standards. When evaluating the evidence offered according to the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Despite this, on an individual level, child outcomes are varied. Ferguson et al ( 2019 ) found only 54% of studies reported favourable outcomes for all participants and Neely et al ( 2021 ) stated 45% of single subject research focusing on communication interventions demonstrated non-effects for child outcomes. Whether this limitation in outcomes is a result of heterogeneity common to a naturalistic teaching model or due to specific difficulties in translating effective naturalistic teaching practices to a telehealth platform (i.e., not being able to readily model behaviour or control the many competing variables which may exist in less structured environments) are important questions to ask.…”
mentioning
confidence: 99%
“…Despite this, on an individual level, child outcomes are varied. Ferguson et al ( 2019 ) found only 54% of studies reported favourable outcomes for all participants and Neely et al ( 2021 ) stated 45% of single subject research focusing on communication interventions demonstrated non-effects for child outcomes. Whether this limitation in outcomes is a result of heterogeneity common to a naturalistic teaching model or due to specific difficulties in translating effective naturalistic teaching practices to a telehealth platform (i.e., not being able to readily model behaviour or control the many competing variables which may exist in less structured environments) are important questions to ask.…”
mentioning
confidence: 99%
“…To determine if gray research is of similar quality to published studies, researchers can assess quality using coding guidelines that includes quality indicators of SCED. Although not a meta-analysis, Neely et al (2021) evaluated the quality of telehealth-mediated behavioral assessments and interventions in their research synthesis using What Works Clearinghouse quality standards (WWC). Quality of research standards were applied to both SCED (Maggin et al, 2012) and group-design research (WWC, 2020).…”
Section: Publication Biasmentioning
confidence: 99%
“…Telehealth offers many advantages to behavior analysts and the clients we serve (Ferguson et al, 2019 ; Neely et al, 2021 ; Tomlinson et al, 2018 ). Telehealth increases access to populations that may be unable to access in-person services for a number of reasons such as living in a geographical region with little to no available services, lack of transportation, or health conditions that make travel or in-person services difficult or risky.…”
mentioning
confidence: 99%
“…The increased accessibility and reduced travel associated with telehealth can result in increased number of clients served with this shortage of skilled providers. Finally, telehealth services have been viewed favorably by parents and caregivers (Ferguson et al, 2019 ; Neely et al, 2021 ; Salome et al, 2017 ; Tomlinson et al, 2018 ). More recently, the global COVID-19 pandemic resulted in a rapid adoption of a telehealth service model as face-to-face professional treatment was frequently deemed unsafe for either the client or the professional (Neely et al, 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation